Senior Teaches Junior (STJ) Approach in Enhancing Arabic Vocabulary through Kitab Af'al: A Case Study in Malaysia - Masnun, Masnun; Hanifansyah, Nur; Khalid, Syarif Muhammad Syaheed bin (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
This study examines the effectiveness of Kitab Af’al in enhancing Arabic vocabulary acquisition using the Senior Teaches Junior (STJ) approach. The research evaluates how structured peer-teaching frameworks foster vocabulary retention and sustainable learning. A mixed method approach was employed, observing 30 students in a classroom setting. Kitab Af’al, featuring 540 verbs, was taught through techniques like spaced repetition, mnemonic devices, and thematic chunking. Data collection included observations, interviews, and documentation analysis. Results show that the combination of Kitab Af’al with the STJ approach significantly improved vocabulary mastery, while also building students' confidence and leadership. Peer-led sessions created a collaborative learning environment and a repository of effective teaching strategies for future application. This study highlights the synergy between traditional resources and innovative methods, offering a cost-effective and sustainable solution for Arabic language acquisition. It underscores the potential of the STJ model to empower students in resource-constrained educational settings.